A composite material for electromagnetic wire insulation layer and a constant tension wrapping molding process for insulation layer
By developing an electromagnetic wire insulating layer composite material composed of a variety of high-performance components and using a constant tension wrap molding process, the problem of degradation of traditional insulating layer materials in harsh environments is solved, and the heat resistance, mechanical strength and environmental adaptability of electromagnetic wires are significantly improved.
Patent Information
- Application Number
- CN202411911406.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-04
AI Technical Summary
The performance of traditional electromagnetic wire insulating layer materials deteriorates under high temperature, high humidity, high frequency or special chemical environments, resulting in aging, cracking or failure of the insulating layer, which in turn causes electrical failures.
A composite material of electromagnetic wire insulating layer composed of polyimide resin, nano-silica modified epoxy resin, flame retardant, conductive filler, toughener and other high-performance components was developed, and a constant tension wrapping molding process was adopted.
It significantly improves the heat resistance, mechanical strength and environmental adaptability of the electromagnetic wires, ensures uniform and dense coating of the insulation layer on the conductor, and improves the safety and reliability of the product.
Smart Images

Figure CN119752178A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of insulating materials, and specifically discloses a composite material for an electromagnetic wire insulation layer and a constant tension wrapping molding process for the insulation layer. Background Art
[0002] In the electrical and electronic fields, electromagnetic wire is the core component of electrical products such as motors, transformers, and inductors. Its performance is directly related to the efficiency, safety, and reliability of the entire electrical system. The insulation layer of the electromagnetic wire is a key part to protect the conductor, prevent current leakage, and ensure the normal transmission of electromagnetic effects. The material selection and preparation process are particularly important.
[0003] Traditional electromagnetic wire insulation materials mostly use single polymers, such as polyvinyl chloride, polyethylene or polyester. Although these materials have certain insulation properties and mechanical strength, their performance is often seriously affected in high temperature, high humidity, high frequency or special chemical environments, causing the insulation layer to age, crack or even fail, which in turn causes electrical failures.
[0004] With the advancement of science and technology and the continuous improvement of performance requirements for electrical products, higher requirements have been placed on the performance of electromagnetic wire insulation materials. Single polymer materials can no longer meet the growing and diverse needs, such as higher heat resistance, better mechanical strength, better electrical performance, and stronger environmental adaptability.
[0005] Therefore, it is particularly important to develop a new type of composite material for electromagnetic wire insulation layer. This composite material should be able to combine the advantages of multiple materials and achieve comprehensive performance improvement through reasonable formula design and preparation process. Summary of the invention
[0006] To solve the above problems, we disclose an electromagnetic wire insulation layer composite material and a constant tension wrapping molding process for the insulation layer.
[0007] The present invention includes the following specific technical solutions:
[0008] A composite material for an electromagnetic wire insulation layer, the composite material comprising the following components in parts by weight:
[0009]
[0010]
[0011] The nano-silicon dioxide modified epoxy resin is prepared by uniformly dispersing nano-silicon dioxide particles in epoxy resin and reacting the mixture.
[0012] The flame retardant is a compound of a phosphazene compound and a nitrogen-based flame retardant;
[0013] The conductive filler is a nanographene sheet;
[0014] The toughening agent is polyetheretherketone.
[0015] Furthermore, in the above-mentioned composite material for electromagnetic wire insulation layer, the polyimide resin is an aromatic polyimide with a high molecular weight, and its weight average molecular weight is between 100,000-300,000.
[0016] Furthermore, in the above-mentioned electromagnetic wire insulation layer composite material, the nano-silicon dioxide modified epoxy resin is prepared by the following steps:
[0017] 1) Surface modification of nano-silica
[0018] Raw material preparation: Select nano-silicon dioxide particles with a particle size of 30±5 nanometers, ensure that its specific surface area is between 150-250 square meters / gram, and the purity is not less than 99.5%. At the same time, prepare anhydrous ethanol as a dispersion medium and an appropriate amount of silane coupling agent KH550;
[0019] Dispersion treatment: Disperse the nano-silicon dioxide particles in anhydrous ethanol and use an ultrasonic disperser for 30-60 minutes to make the nano-silicon dioxide particles evenly dispersed;
[0020] Surface modification: add silane coupling agent KH550 to the nano-silica dispersion under stirring, the mass ratio of silane coupling agent to nano-silica is controlled at about 5 / 100, heat to 60-80°C, react for 2-4 hours, so that the silane coupling agent reacts with the hydroxyl groups on the surface of nano-silica, thereby improving its surface properties;
[0021] Post-treatment: After the reaction is completed, the modified nano-silica is separated by centrifugation, washed with ethanol several times to remove unreacted silane coupling agent and other impurities, and finally, the modified nano-silica is dried at 60-80°C to constant weight for standby use;
[0022] 2) Blending and curing of epoxy resin
[0023] 1) Raw material preparation: Select epoxy resin E-51 and an appropriate amount of anhydride curing agent;
[0024] 2) Blending treatment: Add the modified nano-silicon dioxide into the epoxy resin at a weight ratio of 5-15:100, and use a high-speed mixer or an ultrasonic disperser to fully mix the nano-silicon dioxide and the epoxy resin, so that the nano-silicon dioxide is evenly dispersed in the epoxy resin;
[0025] 3) Curing and molding: Pour the evenly mixed epoxy resin system into the mold, remove the solvent under heating and vacuum conditions, add anhydride for curing, and mix thoroughly. Then, place the mold in an oven and cure at 120-140°C for 1-2 hours to allow the epoxy resin to fully cross-link to form a solid material; after curing, take out the composite material in the mold for subsequent processing and treatment.
[0026] Furthermore, in the above-mentioned electromagnetic wire insulation layer composite material, the antioxidant and the light stabilizer are hindered phenol antioxidant and benzotriazole light stabilizer respectively.
[0027] The present invention also discloses a method for preparing the composite material of the electromagnetic wire insulation layer, comprising the following steps:
[0028] S1 Mixing and Dispersion
[0029] Premixing: Add powdered polyimide resin, nano-silica modified epoxy resin, flame retardant, and toughening agent into a high-speed mixer, heat to 300-500 rpm and premix for 10-20 minutes;
[0030] Dispersion of nanographene sheets: Slowly add the nanographene sheets into the premixed material and continue stirring and mixing at 100-200 rpm for 10-30 minutes;
[0031] Adding antioxidant and light stabilizer: After mixing evenly, add antioxidant and light stabilizer, continue stirring at 200-400rpm to mix so that all components are evenly dispersed;
[0032] S2, molding and curing
[0033] Molding: Pour the evenly mixed material into the mold and shape it according to the required shape and size;
[0034] Curing: Place the formed material in an oven or curing furnace, set the curing temperature to 180-220°C for 2-4 hours, and maintain 1-3 atmospheres of pressure to fully cure the material;
[0035] S3, post-processing
[0036] Cooling and demoulding: After curing is completed, take the material out of the oven or curing furnace and demould it after cooling to room temperature.
[0037] The invention discloses an electromagnetic wire insulation layer strip material, which is prepared by the method.
[0038] The invention discloses a constant tension wrapping molding process for an electromagnetic wire insulation layer, comprising the following steps:
[0039] a. Place the insulation layer of the electromagnetic wire in an environment of 100 to 160°C for more than 6 hours, and preheat the production line oven. The temperature in the oven is set in the range of 350 to 450°C, and the preheating time is at least 30 minutes;
[0040] b. Conductor multi-pass drawing:
[0041] The conductor is drawn and formed by a multi-pass drawing process, and the conductor cross-sectional compression is set within 12% to 28%. The drawing equipment is provided with a high-precision polycrystalline die, and the conductor drawing speed is set within 35 to 90 m / min, and the speed is adaptively adjusted according to the single-pass cross-sectional compression of the conductor.
[0042] c High frequency heating annealing:
[0043] The conductor is subjected to high-frequency heating by using a first high-frequency heater, and the output power and temperature are adjusted by an infrared temperature measuring device to keep the conductor temperature within a range of 250 to 350° C. The first high-frequency heater is placed in an oxygen-free box with a centralized nitrogen supply;
[0044] d. Constant tension wrapping process:
[0045] The conductor with internal stress removed is passed through the wrapping machine, and the conductor is passed through the inner ring of the wrapping machine by active traction;
[0046] Install the magnet wire insulation layer tape on the wrapping head of the wrapping machine, set the speed of the wrapping head within 650 to 1800 r / min, set the pitch of the magnet wire insulation layer tape on the conductor within 2 to 13 mm, and adjust the tension on the conductor within a range of 5 to 18 N;
[0047] The number of the taping heads is 1 to 3, the taping overlap rate of the electromagnetic wire insulation layer tape is 10 to 67%, and the production line speed of the taping process is 2.5 to 11.5 m / min. The specific speed needs to be adaptively adjusted with the rotation speed of the taping head;
[0048] eHigh frequency heating sintering:
[0049] Pass the wrapped conductor through a second high-frequency heater, the temperature of which is set between 370°C and 420°C, so that the magnet wire insulation layer tape is melted and evenly adhered to the conductor;
[0050] The second high-frequency heater and the first high-frequency heater are both provided with an oscillation generating device, the oscillation current is set within 120 to 240A, and the induction frequency is set within 25 to 45kHz; the temperature of the high-frequency heater is adaptively adjusted according to the linear speed of the conductor and the wire passing therethrough;
[0051] fThrough constant temperature water tank:
[0052] After passing through 1 to 3 production line ovens, the conductor is immersed in a constant temperature water tank for step-by-step cooling and curing. The water tank is divided into 3 to 4 sections. The water temperature decreases step by step from the pay-off direction to the take-up direction. The highest temperature is 99°C and the lowest temperature is 40°C. The temperature intervals in each section of the water tank are cooled and replenished with circulating water to ensure temperature stability.
[0053] gCooling and winding:
[0054] The conductor is actively taken up by the take-up frame after passing through the constant temperature water tank, and the tension on the conductor is kept consistent by adjusting the rotation speed of the pay-off frame and the take-up frame.
[0055] Furthermore, the above-mentioned wire is a copper wire.
[0056] Compared with the prior art, the present invention has the following outstanding beneficial effects:
[0057] The present invention develops a composite material for electromagnetic wire insulation layer composed of multiple high-performance components such as polyimide resin, nano-silicon dioxide modified epoxy resin, etc., and combines it with a precise constant tension wrapping molding process to significantly improve the heat resistance, mechanical strength and environmental adaptability of the electromagnetic wire. The composite material preparation process is environmentally friendly and efficient, realizes automated and continuous production, reduces production costs, and ensures uniform and dense coating of the insulation layer on the conductor, improves the safety and reliability of the product, and brings significant technological progress and environmental benefits to the field of electrical products. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 Comparison of room temperature tensile strength of Examples 1-3 and Comparative Examples 1-2;
[0059] Figure 2 Comparison of elongation at break at room temperature between Examples 1-3 and Comparative Examples 1-2;
[0060] Figure 3 Comparison of high temperature tensile strength of Examples 1-3 and Comparative Examples 1-2;
[0061] Figure 4 Comparison of high temperature elongation at break of Examples 1-3 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0062] A composite material for an electromagnetic wire insulation layer, the composite material comprising the following components in parts by weight:
[0063]
[0064] The flame retardant is a 1:1 compound (mass ratio) of hexaphenoxy cyclotriphosphazene and melamine;
[0065] The conductive filler is nanographene sheets (Xianfeng Nano XFQ021);
[0066] The toughening agent is polyetheretherketone PEEK 381G.
[0067] The polyimide resin is P84 NT140G polyimide (Evonik, Germany).
[0068] The antioxidant and light stabilizer are antioxidant 1076 and benzotriazole light stabilizer UV-328 respectively.
[0069] The nano-silicon dioxide modified epoxy resin is prepared by the following steps:
[0070] 1) Surface modification of nano-silica
[0071] Raw material preparation: Select nano-silicon dioxide particles with a particle size of 30±5 nanometers, ensure that its specific surface area is between 150-250 square meters / gram, and the purity is not less than 99.5%. At the same time, prepare anhydrous ethanol as a dispersion medium and an appropriate amount of silane coupling agent KH550;
[0072] Dispersion treatment: Disperse the nano-silicon dioxide particles in anhydrous ethanol and use an ultrasonic disperser for 30-60 minutes to make the nano-silicon dioxide particles evenly dispersed;
[0073] Surface modification: add silane coupling agent KH550 to the nano-silica dispersion under stirring, the mass ratio of silane coupling agent to nano-silica is controlled at 5 / 100, heat to 70°C, react for 3 hours, so that the silane coupling agent reacts with the hydroxyl groups on the surface of the nano-silica, thereby improving its surface properties;
[0074] Post-treatment: After the reaction is completed, the modified nano-silica is separated by centrifugation, washed with ethanol several times to remove unreacted silane coupling agent and other impurities, and finally, the modified nano-silica is dried at 60-80°C to constant weight for standby use;
[0075] 2) Blending and curing of epoxy resin
[0076] 1) Raw material preparation: Select epoxy resin E-51 and an appropriate amount of anhydride curing agent (methyltetrahydrophthalic anhydride);
[0077] 2) Blending treatment: Add the modified nano-silicon dioxide into the epoxy resin at a weight ratio of 1:10, and use a high-speed mixer or an ultrasonic disperser to fully mix the nano-silicon dioxide and the epoxy resin, so that the nano-silicon dioxide is evenly dispersed in the epoxy resin;
[0078] 3) Curing and molding: Pour the evenly mixed epoxy resin system into the mold, remove the solvent under heating and vacuum conditions, add anhydride for curing, and mix thoroughly. Then, place the mold in an oven and cure at 130°C for 1.5 hours to allow the epoxy resin to fully cross-link to form a solid material. After curing is completed, take out the composite material in the mold for subsequent processing and treatment.
[0079] The method for preparing the composite material of the electromagnetic wire insulation layer comprises the following steps:
[0080] S1 Mixing and Dispersion
[0081] Premixing: Add powdered polyimide resin, nano-silica modified epoxy resin, flame retardant, and toughening agent into a high-speed mixer, heat to 400 rpm and premix for 15 minutes;
[0082] Dispersion of nanographene sheets: Slowly add nanographene sheets into the premixed material and continue stirring and mixing at 150 rpm for 20 min;
[0083] Adding antioxidant and light stabilizer: After mixing evenly, add antioxidant and light stabilizer, continue stirring at 300 rpm to make all components evenly dispersed;
[0084] S2, molding and curing
[0085] Molding: Pour the evenly mixed material into the mold and shape it according to the required shape and size;
[0086] Curing: Place the formed material in an oven or curing furnace, set the curing temperature to 200°C for 3 hours, and maintain 2 atmospheres of pressure to fully cure the material;
[0087] S3, post-processing
[0088] Cooling and demoulding: After curing is completed, take the material out of the oven or curing furnace and demould it after cooling to room temperature.
[0089] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0090] Example 1
[0091] A composite material for an electromagnetic wire insulation layer, the composite material comprising the following components in parts by weight:
[0092]
[0093] The flame retardant is a 1:1 compound (mass ratio) of hexaphenoxy cyclotriphosphazene and melamine;
[0094] The conductive filler is nanographene sheets (Xianfeng Nano XFQ021);
[0095] The toughening agent is polyetheretherketone PEEK 381G.
[0096] The polyimide resin is P84 NT140G polyimide (Evonik, Germany).
[0097] The antioxidant and light stabilizer are antioxidant 1076 and benzotriazole light stabilizer UV-328 respectively.
[0098] The nano-silicon dioxide modified epoxy resin is prepared by the following steps:
[0099] 1) Surface modification of nano-silica
[0100] Raw material preparation: Select nano-silicon dioxide particles with a particle size of 30±5 nanometers, ensure that its specific surface area is between 150-250 square meters / gram, and the purity is not less than 99.5%. At the same time, prepare anhydrous ethanol as a dispersion medium and an appropriate amount of silane coupling agent KH550;
[0101] Dispersion treatment: Disperse the nano-silicon dioxide particles in anhydrous ethanol and use an ultrasonic disperser for 30-60 minutes to make the nano-silicon dioxide particles evenly dispersed;
[0102] Surface modification: add silane coupling agent KH550 to the nano-silica dispersion under stirring, the mass ratio of silane coupling agent to nano-silica is controlled at 5 / 100, heat to 70°C, react for 3 hours, so that the silane coupling agent reacts with the hydroxyl groups on the surface of the nano-silica, thereby improving its surface properties;
[0103] Post-treatment: After the reaction is completed, the modified nano-silica is separated by centrifugation, washed with ethanol several times to remove unreacted silane coupling agent and other impurities, and finally, the modified nano-silica is dried at 60-80°C to constant weight for standby use;
[0104] 2) Blending and curing of epoxy resin
[0105] 1) Raw material preparation: Select epoxy resin E-51 and an appropriate amount of anhydride curing agent (methyltetrahydrophthalic anhydride);
[0106] 2) Blending treatment: Add the modified nano-silicon dioxide into the epoxy resin at a weight ratio of 1:10, and use a high-speed mixer or an ultrasonic disperser to fully mix the nano-silicon dioxide and the epoxy resin, so that the nano-silicon dioxide is evenly dispersed in the epoxy resin;
[0107] 3) Curing and molding: Pour the evenly mixed epoxy resin system into the mold, remove the solvent under heating and vacuum conditions, add anhydride for curing, and mix thoroughly. Then, place the mold in an oven and cure at 130°C for 1.5 hours to allow the epoxy resin to fully cross-link to form a solid material. After curing is completed, take out the composite material in the mold for subsequent processing and treatment.
[0108] The method for preparing the composite material of the electromagnetic wire insulation layer comprises the following steps:
[0109] S1 Mixing and Dispersion
[0110] Premixing: Add powdered polyimide resin, nano-silica modified epoxy resin, flame retardant, and toughening agent into a high-speed mixer, heat to 400 rpm and premix for 15 minutes;
[0111] Dispersion of nanographene sheets: Slowly add nanographene sheets into the premixed material and continue stirring and mixing at 150 rpm for 20 min;
[0112] Adding antioxidant and light stabilizer: After mixing evenly, add antioxidant and light stabilizer, continue stirring at 300 rpm to make all components evenly dispersed;
[0113] S2, molding and curing
[0114] Molding: Pour the evenly mixed material into the mold and shape it according to the required shape and size;
[0115] Curing: Place the formed material in an oven or curing furnace, set the curing temperature to 200°C for 3 hours, and maintain 2 atmospheres of pressure to fully cure the material;
[0116] S3, post-processing
[0117] Cooling and demoulding: After curing is completed, take the material out of the oven or curing furnace and demould it after cooling to room temperature.
[0118] Example 2
[0119] A composite material for an electromagnetic wire insulation layer, the composite material comprising the following components in parts by weight:
[0120]
[0121] The flame retardant is a 1:1 compound (mass ratio) of hexaphenoxy cyclotriphosphazene and melamine;
[0122] The conductive filler is nanographene sheets (Xianfeng Nano XFQ021);
[0123] The toughening agent is polyetheretherketone PEEK 381G.
[0124] The polyimide resin is P84 NT140G polyimide (Evonik, Germany).
[0125] The antioxidant and light stabilizer are antioxidant 1076 and benzotriazole light stabilizer UV-328 respectively.
[0126] The nano-silicon dioxide modified epoxy resin is prepared by the following steps:
[0127] 1) Surface modification of nano-silica
[0128] Raw material preparation: Select nano-silicon dioxide particles with a particle size of 30±5 nanometers, ensure that its specific surface area is between 150-250 square meters / gram, and the purity is not less than 99.5%. At the same time, prepare anhydrous ethanol as a dispersion medium and an appropriate amount of silane coupling agent KH550;
[0129] Dispersion treatment: Disperse the nano-silicon dioxide particles in anhydrous ethanol and use an ultrasonic disperser for 30-60 minutes to make the nano-silicon dioxide particles evenly dispersed;
[0130] Surface modification: add silane coupling agent KH550 to the nano-silica dispersion under stirring, the mass ratio of silane coupling agent to nano-silica is controlled at 5 / 100, heat to 70°C, react for 3 hours, so that the silane coupling agent reacts with the hydroxyl groups on the surface of the nano-silica, thereby improving its surface properties;
[0131] Post-treatment: After the reaction is completed, the modified nano-silica is separated by centrifugation, washed with ethanol several times to remove unreacted silane coupling agent and other impurities, and finally, the modified nano-silica is dried at 60-80°C to constant weight for standby use;
[0132] 2) Blending and curing of epoxy resin
[0133] 1) Raw material preparation: Select epoxy resin E-51 and an appropriate amount of anhydride curing agent (methyltetrahydrophthalic anhydride);
[0134] 2) Blending treatment: Add the modified nano-silicon dioxide into the epoxy resin at a weight ratio of 1:10, and use a high-speed mixer or an ultrasonic disperser to fully mix the nano-silicon dioxide and the epoxy resin, so that the nano-silicon dioxide is evenly dispersed in the epoxy resin;
[0135] 3) Curing and molding: Pour the evenly mixed epoxy resin system into the mold, remove the solvent under heating and vacuum conditions, add anhydride for curing, and mix thoroughly. Then, place the mold in an oven and cure at 130°C for 1.5 hours to allow the epoxy resin to fully cross-link to form a solid material. After curing is completed, take out the composite material in the mold for subsequent processing and treatment.
[0136] The method for preparing the composite material of the electromagnetic wire insulation layer comprises the following steps:
[0137] S1 Mixing and Dispersion
[0138] Premixing: Add powdered polyimide resin, nano-silica modified epoxy resin, flame retardant, and toughening agent into a high-speed mixer, heat to 400 rpm and premix for 15 minutes;
[0139] Dispersion of nanographene sheets: Slowly add nanographene sheets into the premixed material and continue stirring and mixing at 150 rpm for 20 min;
[0140] Adding antioxidant and light stabilizer: After mixing evenly, add antioxidant and light stabilizer, continue stirring at 300 rpm to make all components evenly dispersed;
[0141] S2, molding and curing
[0142] Molding: Pour the evenly mixed material into the mold and shape it according to the required shape and size;
[0143] Curing: Place the formed material in an oven or curing furnace, set the curing temperature to 200°C for 3 hours, and maintain 2 atmospheres of pressure to fully cure the material;
[0144] S3, post-processing
[0145] Cooling and demoulding: After curing is completed, take the material out of the oven or curing furnace and demould it after cooling to room temperature.
[0146] Example 3
[0147] A composite material for an electromagnetic wire insulation layer, the composite material comprising the following components in parts by weight:
[0148]
[0149] The flame retardant is a 1:1 compound (mass ratio) of hexaphenoxy cyclotriphosphazene and melamine;
[0150] The conductive filler is nanographene sheets (Xianfeng Nano XFQ021);
[0151] The toughening agent is polyetheretherketone PEEK 381G.
[0152] The polyimide resin is P84 NT140G polyimide (Evonik, Germany).
[0153] The antioxidant and light stabilizer are antioxidant 1076 and benzotriazole light stabilizer UV-328 respectively.
[0154] The nano-silicon dioxide modified epoxy resin is prepared by the following steps:
[0155] 1) Surface modification of nano-silica
[0156] Raw material preparation: Select nano-silicon dioxide particles with a particle size of 30±5 nanometers, ensure that its specific surface area is between 150-250 square meters / gram, and the purity is not less than 99.5%. At the same time, prepare anhydrous ethanol as a dispersion medium and an appropriate amount of silane coupling agent KH550;
[0157] Dispersion treatment: Disperse the nano-silicon dioxide particles in anhydrous ethanol and use an ultrasonic disperser for 30-60 minutes to make the nano-silicon dioxide particles evenly dispersed;
[0158] Surface modification: add silane coupling agent KH550 to the nano-silica dispersion under stirring, the mass ratio of silane coupling agent to nano-silica is controlled at 5 / 100, heat to 70°C, react for 3 hours, so that the silane coupling agent reacts with the hydroxyl groups on the surface of the nano-silica, thereby improving its surface properties;
[0159] Post-treatment: After the reaction is completed, the modified nano-silica is separated by centrifugation, washed with ethanol several times to remove unreacted silane coupling agent and other impurities, and finally, the modified nano-silica is dried at 60-80°C to constant weight for standby use;
[0160] 2) Blending and curing of epoxy resin
[0161] 1) Raw material preparation: Select epoxy resin E-51 and an appropriate amount of anhydride curing agent (methyltetrahydrophthalic anhydride);
[0162] 2) Blending treatment: Add the modified nano-silicon dioxide into the epoxy resin at a weight ratio of 1:10, and use a high-speed mixer or an ultrasonic disperser to fully mix the nano-silicon dioxide and the epoxy resin, so that the nano-silicon dioxide is evenly dispersed in the epoxy resin;
[0163] 3) Curing and molding: Pour the evenly mixed epoxy resin system into the mold, remove the solvent under heating and vacuum conditions, add anhydride for curing, and mix thoroughly. Then, place the mold in an oven and cure at 130°C for 1.5 hours to allow the epoxy resin to fully cross-link to form a solid material. After curing is completed, take out the composite material in the mold for subsequent processing and treatment.
[0164] The method for preparing the composite material of the electromagnetic wire insulation layer comprises the following steps:
[0165] S1 Mixing and Dispersion
[0166] Premixing: Add powdered polyimide resin, nano-silica modified epoxy resin, flame retardant, and toughening agent into a high-speed mixer, heat to 400 rpm and premix for 15 minutes;
[0167] Dispersion of nanographene sheets: Slowly add nanographene sheets into the premixed material and continue stirring and mixing at 150 rpm for 20 min;
[0168] Adding antioxidant and light stabilizer: After mixing evenly, add antioxidant and light stabilizer, continue stirring at 300 rpm to make all components evenly dispersed;
[0169] S2, molding and curing
[0170] Molding: Pour the evenly mixed material into the mold and shape it according to the required shape and size;
[0171] Curing: Place the formed material in an oven or curing furnace, set the curing temperature to 200°C for 3 hours, and maintain 2 atmospheres of pressure to fully cure the material;
[0172] S3, post-processing
[0173] Cooling and demoulding: After curing is completed, take the material out of the oven or curing furnace and demould it after cooling to room temperature.
[0174] Comparative Example 1
[0175] This comparative example uses epoxy resin E-51 without modification. The rest is the same as in Example 2.
[0176] Comparative Example 2
[0177] Common polyimide insulation materials available on the market.
[0178] Preparation Example
[0179] The electromagnetic wire insulation layer composite materials (electromagnetic wire insulation layer strips) of Examples 1-3 and Comparative Examples 1-2 were prepared into electromagnetic wire insulation layers according to the following process:
[0180] a. Place the insulation layer of the electromagnetic wire in an environment of 130°C and bake for 8 hours, and preheat the production line oven. The temperature in the oven is set at 370°C and the preheating time is 1 hour.
[0181] b. Conductor multi-pass drawing:
[0182] The copper conductor is drawn and formed by a multi-pass drawing process, and the conductor cross-section compression is set within 20%; a high-precision polycrystalline die is set in the drawing equipment, and the conductor drawing speed is set at 50m / min;
[0183] c High frequency heating annealing:
[0184] The conductor is subjected to high-frequency heating by using a first high-frequency heater, and the output power and temperature are adjusted by an infrared temperature measuring device to keep the conductor temperature within a range of 250 to 350° C. The first high-frequency heater is placed in an oxygen-free box with a centralized nitrogen supply;
[0185] d. Constant tension wrapping process:
[0186] The conductor with internal stress removed is passed through the wrapping machine, and the conductor is passed through the inner ring of the wrapping machine by active traction;
[0187] Install the electromagnetic wire insulation layer tape on the wrapping head of the wrapping machine, set the speed of the wrapping head to 1000r / min, set the pitch of the electromagnetic wire insulation layer tape on the conductor to 7mm, and the tension adjustment range on the conductor to 12N;
[0188] The number of taping heads is 2, the taping overlap rate of the electromagnetic wire insulation layer tape is 50-60%, and the production line speed of the taping process is 5.5-7.5m / min. The specific speed needs to be adaptively adjusted with the rotation speed of the taping head;
[0189] eHigh frequency heating sintering:
[0190] Pass the wrapped conductor through a second high-frequency heater, the temperature of which is set at 390°C, so that the magnet wire insulation layer tape melts and evenly adheres to the conductor;
[0191] The second high-frequency heater and the first high-frequency heater are both provided with an oscillation generating device, the oscillation current is set within 120 to 240A, and the induction frequency is set within 25 to 45kHz; the temperature of the high-frequency heater is adaptively adjusted according to the linear speed of the conductor and the wire passing therethrough;
[0192] fThrough constant temperature water tank:
[0193] After passing through two production line ovens, the conductor is immersed in a constant temperature water tank for step-by-step cooling and curing. The water tank is divided into four sections, and the water temperature decreases step by step from the pay-off direction to the take-up direction. The highest temperature is 99°C and the lowest temperature is 40°C. The temperature intervals in each section of the water tank are cooled and replenished with circulating water to ensure temperature stability.
[0194] gCooling and winding:
[0195] The conductor is actively taken up by the take-up frame after passing through the constant temperature water tank, and the tension on the conductor is kept consistent by adjusting the rotation speed of the pay-off frame and the take-up frame.
[0196] Test Case
[0197] The electromagnetic wire insulation layers of Examples 1-3 and Comparative Examples 1-2 were tested, including tensile strength and elongation at break at room temperature; tensile strength and elongation at break after high temperature (80°C) treatment for 168 hours; and salt spray test (GB / T 2423.17-2008 "Basic Environmental Testing Procedures for Electrical and Electronic Products Test Ka: Salt Spray Test Method"), 5% sodium chloride concentration, 60°C, 100 hours, and observation of surface corrosion.
[0198] The results are shown in Table 1 and Figure 1-4 shown.
[0199] Table 1: Performance Test
[0200]
[0201]
[0202] From the results in Table 1 above, it can be seen that Examples 1-3 of the present invention have excellent mechanical properties at room temperature and high temperature, excellent heat resistance and corrosion resistance; they are very suitable for use as the insulation layer of electromagnetic wire in harsh working environments. From the comparison between Example 2 and Comparative Example 1, it can be seen that after the epoxy resin E-51 is modified with silicon dioxide, unlike the expected small progress, the mechanical properties of the prepared insulation layer at room temperature and high temperature are greatly improved in coordination with other components of the present invention, and the corrosion resistance is also improved.
[0203] It can be seen from the above embodiments that the present invention significantly improves the heat resistance, mechanical strength and environmental adaptability of electromagnetic wires by developing a composite material for electromagnetic wire insulation layer composed of multiple high-performance components such as polyimide resin, nano-silicon dioxide modified epoxy resin, etc., and combining it with a precise constant tension wrapping molding process. The composite material preparation process is environmentally friendly and efficient, realizes automated and continuous production, reduces production costs, and ensures uniform and dense coating of the insulation layer on the conductor, improves the safety and reliability of the product, and brings significant technological progress and environmental benefits to the field of electrical products.
[0204] The above are only a few preferred embodiments of the present invention, which are described in a more specific and detailed manner, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A composite material for an electromagnetic wire insulation layer, characterized in that: The composite material consists of the following components by weight: Polyimide resin 50-70 parts Nano-silicon dioxide modified epoxy resin 10-25 parts Flame retardant 5-15 parts Conductive filler 2-8 parts Toughener 3-10 parts 0.5-3 parts of antioxidant Light stabilizer 0.5-2 parts The nano-silicon dioxide modified epoxy resin is prepared by uniformly dispersing nano-silicon dioxide particles in epoxy resin and reacting the mixture. The flame retardant is a compound of a phosphazene compound and a nitrogen-based flame retardant; The conductive filler is a nanographene sheet; The toughening agent is polyetheretherketone.
2. The composite material for electromagnetic wire insulation layer according to claim 1, characterized in that: The polyimide resin is an aromatic polyimide with a high molecular weight, and the weight average molecular weight thereof is between 100,000 and 300,000.
3. The composite material for electromagnetic wire insulation layer according to claim 1, characterized in that: The nano-silicon dioxide modified epoxy resin is prepared by the following steps: 1) Surface modification of nano-silica Raw material preparation: Select nano-silicon dioxide particles with a particle size of 30±5 nanometers, ensure that its specific surface area is between 150-250 square meters / gram, and the purity is not less than 99.5%. At the same time, prepare anhydrous ethanol as a dispersion medium and an appropriate amount of silane coupling agent KH550; Dispersion treatment: Disperse the nano-silicon dioxide particles in anhydrous ethanol and use an ultrasonic disperser for 30-60 minutes to make the nano-silicon dioxide particles evenly dispersed; Surface modification: add silane coupling agent KH550 to the nano-silica dispersion under stirring, the mass ratio of silane coupling agent to nano-silica is controlled at about 5 / 100, heat to 60-80°C, react for 2-4 hours, so that the silane coupling agent reacts with the hydroxyl groups on the surface of nano-silica, thereby improving its surface properties; Post-treatment: After the reaction is completed, the modified nano-silica is separated by centrifugation, washed with ethanol several times to remove unreacted silane coupling agent and other impurities, and finally, the modified nano-silica is dried at 60-80°C to constant weight for standby use; 2) Blending and curing of epoxy resin 1) Raw material preparation: Select epoxy resin E-51 and an appropriate amount of anhydride curing agent; 2) Blending treatment: Add the modified nano-silicon dioxide into the epoxy resin at a weight ratio of 5-15:100, and use a high-speed mixer or ultrasonic disperser to fully mix the nano-silicon dioxide and the epoxy resin, so that the nano-silicon dioxide is evenly dispersed in the epoxy resin; 3) Curing and molding: Pour the evenly mixed epoxy resin system into the mold, remove the solvent under heating and vacuum conditions, add anhydride for curing, and mix thoroughly. Then, place the mold in an oven and cure at 120-140°C for 1-2 hours to allow the epoxy resin to fully cross-link to form a solid material. After curing is completed, take out the composite material in the mold for subsequent processing and treatment.
4. The composite material for electromagnetic wire insulation layer according to claim 1, characterized in that: The antioxidant and light stabilizer are hindered phenol antioxidant and benzotriazole light stabilizer respectively.
5. The method for preparing the composite material for electromagnetic wire insulation layer according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1 Mixing and Dispersion Premixing: Add powdered polyimide resin, nano-silica modified epoxy resin, flame retardant, and toughening agent into a high-speed mixer, heat to 300-500 rpm and premix for 10-20 minutes; Dispersion of nanographene sheets: Slowly add the nanographene sheets into the premixed material and continue stirring and mixing at 100-200 rpm for 10-30 minutes; Adding antioxidant and light stabilizer: After mixing evenly, add antioxidant and light stabilizer, continue stirring at 200-400rpm to mix so that all components are evenly dispersed; S2, molding and curing Molding: Pour the evenly mixed material into the mold and shape it according to the required shape and size; Curing: Place the formed material in an oven or curing furnace, set the curing temperature to 180-220°C for 2-4 hours, and maintain 1-3 atmospheres of pressure to fully cure the material; S3, post-processing Cooling and demoulding: After curing is completed, take the material out of the oven or curing furnace and demould it after cooling to room temperature.
6. An electromagnetic wire insulation strip, characterized in that: Prepared by the method described in claim 5.
7. A constant tension wrapping molding process for an electromagnetic wire insulation layer, characterized in that: The following steps are involved: a. Place the electromagnetic wire insulation strip in an environment of 100 to 160°C for more than 6 hours, and preheat the production line oven. The temperature in the oven is set in the range of 350 to 450°C, and the preheating time is at least 30 minutes; b. Conductor multi-pass drawing: The conductor is drawn and formed by a multi-pass drawing process, and the conductor cross-sectional compression is set within 12% to 28%. The drawing equipment is equipped with a high-precision polycrystalline die, and the conductor drawing speed is set within 35 to 90 m / min. The speed is adaptively adjusted according to the single-pass cross-sectional compression of the conductor. c High frequency heating annealing: The conductor is subjected to high-frequency heating by using a first high-frequency heater, and the output power and temperature are adjusted by an infrared temperature measuring device to keep the conductor temperature within a range of 250 to 350° C. The first high-frequency heater is placed in an oxygen-free box with a centralized nitrogen supply; d. Constant tension wrapping process: The conductor with internal stress removed is passed through the wrapping machine, and the conductor is passed through the inner ring of the wrapping machine by active traction; Install the magnet wire insulation layer tape on the wrapping head of the wrapping machine, set the speed of the wrapping head within 650 to 1800 r / min, set the pitch of the magnet wire insulation layer tape on the conductor within 2 to 13 mm, and adjust the tension on the conductor within a range of 5 to 18 N; The number of taping heads is 1 to 3, the taping overlap rate of the electromagnetic wire insulation layer tape is 10 to 67%, and the production line speed of the taping process is 2.5 to 11.5 m / min. The specific speed needs to be adaptively adjusted with the rotation speed of the taping head; eHigh frequency heating sintering: Pass the wrapped conductor through a second high-frequency heater, the temperature of which is set between 370°C and 420°C, so that the magnet wire insulation layer tape is melted and evenly adhered to the conductor; The second high-frequency heater and the first high-frequency heater are both provided with an oscillation generating device, the oscillation current is set within 120 to 240A, and the induction frequency is set within 25 to 45kHz; the temperature of the high-frequency heater is adaptively adjusted according to the linear speed of the conductor and the wire passing therethrough; fThrough constant temperature water tank: After passing through 1 to 3 production line ovens, the conductor is immersed in a constant temperature water tank for step-by-step cooling and curing. The water tank is divided into 3 to 4 sections. The water temperature decreases step by step from the pay-off direction to the take-up direction. The highest temperature is 99°C and the lowest temperature is 40°C. The temperature intervals in each section of the water tank are cooled and replenished with circulating water to ensure temperature stability. gCooling and winding: The conductor is actively taken up by the take-up frame after passing through the constant temperature water tank, and the tension on the conductor is kept consistent by adjusting the rotation speed of the pay-off frame and the take-up frame.
8. The molding process according to claim 7, characterized in that: The wire is a copper wire.